Policy Strategy to Combat Illegal Firearms Smuggling as Transnational Organized Crime into Indonesia - Prasetiyo, Anggy (Jurnal Ilmu Kepolisian, 2024)
Illegal firearms smuggling represents a significant threat to Indonesia's national and regional security. This study seeks to evaluate the Indonesian government’s policies and strategies for mitigating this transnational crime, measure their effectiveness, and uncover persistent challenges. By employing a literature-based approach combined with case data and policy analysis, the study delves into the geographical and institutional complexities that influence the dynamics of arms smuggling in Indonesia. The findings reveal that, despite considerable legislative and operational efforts, gaps in monitoring and enforcement remain, enabling smuggling activities to persist. Key challenges include limited resources, inadequate inter-agency coordination, and the pressing need for stronger international collaboration. To address these issues, the study recommends enhancing inter-agency and international partnerships, improving law enforcement capacity, and launching public awareness campaigns to bridge existing gaps. This research provides actionable insights for policymakers, law enforcement agencies, and academics, supporting the development of a more integrated and effective approach to combat illegal firearms smuggling.